Conceptualising Clinical Legal Education In Legal Pedagogy Of India: Significance And Challenges - et. al., Priyashikha Rai, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Legal pedagogy has evolved to produce more efficient and dynamic practitioners of law. The Bar Council of India (BCI) has been instrumental in regulating legal education standards and monitoring the law colleges that issue law degrees since adopting the Advocates Act of 1961. The legal profession demands more than mere traditional classroom teaching-learning methods. Clinical Legal Education is a concept that enables the students to learn through practical experience. It also disseminates the passion of public interest and social services amongst law students, and not just with the pedagogic method. Legal Aid, therefore, closely engages with Clinical Legal Education. The authors observe that a prevailing theory-practice gap in legal pedagogy can be bridged effectively through institutional mechanisms. This mission of producing justice-oriented legal professionals is paired with the massification of legal education.